RITUAL PENYEMBUHAN PADA MASYARAKAT SUKU DAYAK DI KALIMANTAN TENGAH DALAM NASKAH KUNO “AMIROE” - Syila Fadilah; Andi Nunun May Rizky; Erna Wahyuni; Nurul Hanna Fauziyyah (Smart Education, 2025)
Abstract: This study aims to examine the practices and symbolic meanings within the healing rituals of the Dayak tribe in Central Kalimantan, as documented in the ancient manuscript